Analisis Faktor-Faktor Penyebab Burnout pada Karyawan Generasi Z: Sebuah Studi Literatur - Putri Utami; Siti Zahra Zafira; Yuni Widiyastuti; Merika Setiawati (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2025)
Burnout has become a significant issue in the workplace, particularly among Generation Z employees who are characterized by high adaptability to technology but also vulnerability to work pressure and psychological stress. This study aims to analyze the factors contributing to burnout among Generation Z employees through a literature review approach. The method used is a systematic literature study by reviewing scientific articles, journals, and relevant publications related to burnout and Generation Z in the work context. The analysis results indicate that burnout among Generation Z employees is influenced by several dominant factors, including excessive workload, work-life imbalance, high job demands, lack of social support, role ambiguity, and limited opportunities for self-development. In addition, the use of digital technology without adequate boundaries also contributes to increased work stress. These findings suggest the importance of organizational strategies in managing workload, improving psychological well-being, and creating a supportive work environment to reduce burnout levels among Generation Z employees. This study is expected to serve as a reference for organizations and researchers in understanding and addressing burnout issues in the younger workforce.